Optimización de los modelos de las nanostore: administración de la cadena de suministros mediante las innovaciones en la Industria 4.0 - Acevedo-Amaya, Mario Roberto; Ortega-Jimenez, Cesar Humberto (LACCEI, 2024)
The fourth industrial revolution has brought changes, tools, and technologies that boost operational performance. In nanostores, the innovations and applications of Industry 4.0 allow them to have new technological applications to connect in real-time with the supplier, have more significant and better access to credit, offer new payment methods to customers, and optimize their business model, move from a traditional model to an integrated model with suppliers and customers. Therefore, a quantitative, empirical study was developed using a database of 661 units to analyze the impact of Industry 4.0 on optimizing the business model along the supply chain. We used the hierarchical regression method to test the hypotheses. The results show that there is a positive and significant relationship between the optimization of business models and Industry 4.0 when they are applied to the Supply Chain, even though the level of technological inclusion is expensive and is not within reach of all nanostores. We determined that in the short term, the innovations of Industry 4.0 will not only integrate the supplier company with the nano store but will directly connect the supplier company with the client and the client with the nano store, becoming warehouses adjusted to the client’s needs.